Evolution of the marginal based remuneration of the Portuguese transmission company from 1998 to 2004 - J. Tomé Saraiva (2009)
Back in 1999, the Power Systems Unit of INESC Porto concluded a consultancy study to estimate the remuneration that could be obtained by the Portuguese transmission provider using Short Term Marginal Prices. By that time the Regulatory Agency decided not to include a marginal based term on the Transmission Network Tariffs. However, that study was updated using information about the operation of the network in 2001 and recently it was concluded a new version of this study using information from 2004. This paper describes the models used in these studies, the assumptions that were adopted and the evolution of the marginal based remuneration that the Portuguese transmission provider could obtain if a marginal based tariff term existed. This evolution is important in order to get insight on the congestion level of the transmission network and on how neutral the transmission network is behaving in being able to physically implement the dispatches prepared by the Market Operator or related with bilateral contracts.